Meninjau Kembali Prinsip dan Perencanaan Supervisi Pendidikan Sebagai Pengawasan dalam Pendidikan yang Bersifat Pembinaan - Muhammad Amin Fathih (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
Educational supervision by some teachers is considered frightening, finding faults and fulfilling administrative documents only. This cannot be separated from the lack of supervisors in properly planning and understanding the objectives and principles of supervision. Educational supervision aims to provide supervision and guidance to teachers to improve their skills and professionalism in building good teaching and learning situations. The principle of educational supervision is based on the development of teacher potential, coaching, cooperative, constructive, realistic, and far from authoritarian. Supervision planning is the activity of preparing teacher assistance documents, starting from the objectives, programs, time allocation, and targets, as well as managing existing resources so that monitoring activities can achieve the expected. Aspects that need to be considered in supervision include; 1) Coaching, meaning that supervisors must be able to develop a coaching program in terms of processes, assessments, and targets to be achieved in the implementation of supervision. 2) Monitoring, this area should not be outside the provisions of applicable education standards. 3) Assessment, carried out objectively based on the teacher's performance and the teacher's transformation process towards his students. 4) Teacher coaching is a follow-up to the implementation of educational supervision.